2020
DOI: 10.3389/fpsyt.2020.553269
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cingulate Cortex Glutamate Levels Are Related to Response to Initial Antipsychotic Treatment in Drug-Naive First-Episode Schizophrenia Patients

Abstract: The glutamatergic system has previously been shown to be involved in the pathophysiology of schizophrenia and the mechanisms of action of antipsychotic treatment. The present study aimed to investigate the relationship between the levels of glutamate (Glu) or Glu/total creatine (Glu/Cr+PCr) in the anterior cingulate cortex (ACC) and psychiatric symptoms as well as the response to antipsychotic treatment. We performed proton magnetic resonance spectroscopy (1 H-MRS) to measure Glu and Glu/Cr+PCr in the ACC of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Both Olbrich et al (2008) and Li et al (2020) found significant negative correlation between frontal Glu levels in FEP patients, and their scores on BACS and PANNS-N respectively. This effect was not replicated by Bartolomeo et al (2019) who also failed to find a significant relationship with the mismatch negativity results.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Both Olbrich et al (2008) and Li et al (2020) found significant negative correlation between frontal Glu levels in FEP patients, and their scores on BACS and PANNS-N respectively. This effect was not replicated by Bartolomeo et al (2019) who also failed to find a significant relationship with the mismatch negativity results.…”
Section: Resultsmentioning
confidence: 88%
“…Two studies ( Li et al, 2020 ; Olbrich et al, 2008 ) reported negative correlations between frontal Glu levels and negative symptom severity with lower Glu levels being associated with more negative symptoms. In contrast, Jauhar et al (2018) did not find a significant correlation between medial frontal Glu levels and negative symptoms, but a negative correlation between Glu and positive symptom severity, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, antipsychotic-naïve schizophrenia patients had increased dorsal striatal glutamate, which normalized with prospective risperidone treatment ( 7 ). However, a recent study in antipsychotic-naïve schizophrenia failed to detect any differences in anterior cingulate glutamate ( 6 ). Furthermore, two 7T studies of the anterior cingulate in chronically-ill patients found glutamate reductions ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia studies using single-voxel 1 H-MRS suggest glutamate increases in "basal ganglia" (3) though more recent studies at 7T in early antipsychotic-treated psychosis found prefrontal glutamate reductions (4,5). Furthermore, nevertreated schizophrenia patients had no glutamate differences relative to healthy control subjects in dorsal anterior cingulate (6), but increases have been documented in the dorsal striatum in this population (7). Like schizophrenia, bipolar-I is a chronic, neurodevelopmental disorder, often presents with psychotic symptoms, and is commonly treated with antipsychotic medications (8).…”
Section: Introductionmentioning
confidence: 99%